EFL Teachers’ Perspectives Towards Self-regulation in Language Learning - Yılmaz, Gülşah; Akyıldız, Seçil Tümen (Behçet ORAL, 2023)
The learner-centered approach of self-regulated learning (SRL), long regarded as an effective approach in English as a Foreign Language (EFL), encompasses both cognitive and affective components. As the world changes rapidly, learners need to develop the skills and strategies they need to learn independently. SRL is therefore essential to prepare students for the challenges of 21st century life and the workplace by preparing them to become lifelong learners. Educators play a key role in promoting and nurturing SRL in their classrooms, since they are one of the most important stakeholders guiding students in the learning process. The beliefs of EFL teachers are crucial in this regard. In the context of EFL in Turkey, there are comparatively few studies on SRL. In order to better understand Turkish EFL teachers' attitudes on self-regulated learning, this study looked into their perspectives. The study is a qualitative research investigating the perspectives of Turkish EFL teachers towards SRL I language teaching.The participants of the the study consisted of 15 EFL teachers working at secondary schools in Elazığ. The findings of the study provided remarkable information about Turkish English teachers' beliefs and thoughts on SRL. The findings show that some SRL misconceptions and a lack of knowledge exist among EFL teachers. Additionally, it was discovered that their behaviors and beliefs weren't consistent. Finally, both facilitating and constraining factors affecting teachers’ belief about SRL were analysed in terms of context-level, teacher-level, student-level and parent-level. This study explored Turkish EFL teachers’ beliefs and thoughts on SRL and it will contribute to the field with its valuable results.
Keywords: Specialist Studies in Education (Other); Eğitim Üzerine Çalışmalar (Diğer)